The Efforts of Salih Ghilous in Establishing Cognitive Linguistics in Algeria: The Book “Studies in Cognitive Linguistics” as a Model - arbawi, fatimazohra; mendil, naouel (El Omda in Linguistics and Discourse Analysis, 2023)
Abstract this studs sheds ligt on the efforts of Dr Salih Ghalius in modern Gnostic linguistic thout through his books and scientific journals tagged with the Omda for the Principles of Gnostic linguistics Somethinkers testify to Africa the term has caused problems according to the stdies have varied and som thinkers testify to the precedence of Algeria in its Application of this modern linguistic field especially Dr.Khaled kazem Al-Iraki .for this reason our study goes up to shed light on the research writing of the Algerian professor Saleh Ghalius Alarfania and showing the extent of the development of linguistic research at the University of Algeria.